2022
DOI: 10.1007/s11356-022-21151-8
|View full text |Cite
|
Sign up to set email alerts
|

Extreme environmental temperatures and motorcycle crashes: a time-series analysis

Abstract: Extreme temperature could affect traffic crashes by influencing road safety, vehicle performance, and drivers’ behavior and abilities. Studies evaluating the impacts of extreme temperatures on the risk of traffic crashes have mainly overlooked the potential role of vehicle air conditioners. The aim of this study, therefore, was to evaluate the effect of exposure to extreme cold and hot temperatures on seeking medical attention due to motorcycle crashes. The study was conducted in Iran by using medical attendan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…Previous study have shown that high and low temperatures were obviously correlated with RTIs, and the effect of extreme hot weather was significantly higher than that of extreme cold weather ( 27 ), which was consistent with the results of this paper on the impact of high temperatures. Wu et al ( 16 ) showed that there was a significant positive correlation between fatal traffic accidents and heat waves in the United States.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study have shown that high and low temperatures were obviously correlated with RTIs, and the effect of extreme hot weather was significantly higher than that of extreme cold weather ( 27 ), which was consistent with the results of this paper on the impact of high temperatures. Wu et al ( 16 ) showed that there was a significant positive correlation between fatal traffic accidents and heat waves in the United States.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found elevated risks not only on the same day, but also delayed effects of up to a week. Other studies have also found delayed effects (Hou et al, 2022;Lee et al, 2020;Liang et al, 2021;Zare Sakhvidi et al, 2022). This suggests that the mechanisms leading to those increases in risk are not restricted only to the direct effect of temperature at the time of the crash.…”
Section: Discussionmentioning
confidence: 88%
“…A study in Pakistan reported an increase in the risk of road fatalities of 3.6% for a 1% increase in temperature (Ali et al, 2020). A study in Iran focused specifically on motorcycle crashes and found a 20% increase in risk when comparing the 99th percentile of temperature with the temperature of minimum crashes (Zare Sakhvidi et al, 2022). Finally, a countrywide study in Italy found increases of 12% and of 6% when comparing the 75th and 99th percentiles of temperature for overall road crashes and work-related road crashes, respectively (Gariazzo et al,Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations